Pilgrimage to Mecca and "radical" islam : new trends from Sub-Saharan Africa - (:unkn) unknown (My University, 2017)
In sub-Saharan Africa, the pilgrimage to Mecca is an old tradition, and the Holy City has a global impact on the mobility of Muslims and the circulation of Islamic ideas. However, the proportion of sub-Saharan Muslims making the pilgrimage to Mecca has been decreasing, especially from Nigeria, the most populated country on the continent. Indeed, the opportunities to visit Mecca are limited by internal and external constraints that depend on many political, economic, and social factors. As a result, the yearly numbers of pilgrims do not say much about religiosity or the propensity for jihadist violence. In this regard, it is more important to understand from a historical point of view the role of Mecca in the so-called radicalization of Islam in Africa south of the Sahara.
Keywords: African Research